Measuring the acceptance and adoption of e-learning by academic staff - Al-Alak B.A.; Alnawas I.A.M. (2023)
The aim of the study was to investigate Jordanian lecturers' attitudes towards the adoption of e-learning system. A number of hypotheses were formulated for this purpose. The findings of the study show that there existed positive relationship between perceived usefulness, perceived ease of use, computer knowledge, management support and intention to adopt. Whereas there existed negative relationship between normative pressure, computer anxiety and intention to adopt. Based on the results a number of recommendations were proposed, and suggestions for future studies were made.